Library services and resoure sharing activities of non-government organizations (NGOs) on Women in Quezon City - Dery, Dorothy S. (2002)
Resource sharing programs have enabled libraries to achieve a more cost-efficient and maximized library services to meet users' various information and research needs. This study attempted to determine the feasibility of establishing a library resource-sharing and networking program among non-government organizations (NGOs) on women that are based in Quezon City. The study also focused on the information resources, services, manpower, budget, clientele and library cooperation programs. The objectives of the study were to know the nature of the library collection of the women NGOs in Q.C.; determine the availability of information resources which can be shared in terms of scope and area of specialization; find out the cooperative activities already being implemented and the problems encountered and determine how these libraries can organize a resource sharing program, with the possibility of establishing an automated library network among the women NGO libraries in Q.C.